Keeping Patients Safer: Reviewing Predictors of Success and Failure of Short Peripheral Intravenous Catheters. Issue 4 (July 2022) - DeVries, Michelle; Scott, Nancy
Abstract : In 2014, a large urban community hospital adopted protected clinical indication practices as a quality improvement project. It then undertook a research study to examine bedside practices with short peripheral catheters, which included direct observation at the bedside once weekly for 6 months. A total of 4305 catheters were observed and remained in place for a total of 23 423 days. Fifty six percent of devices remained in place beyond 96 hours. The overall rate of peripheral bloodstream infection in patients enrolled in the study was 0.12/1000 peripheral intravenous days. Significant differences were noted based on which department placed the catheter, as well as which department cared for the patient during hospitalization. Patients admitted to step-down critical care units had the highest completion of therapy rates; however, those being cared for in medical/surgical units had the best outcomes. Devices placed in the emergency department had a higher successful dwell rate than those placed in critical care units. Twenty-gauge catheters were found to have the highest successful dwell rate, as well as insertion sites that were observed to be within normal limits during the weekly observation. Dressings that were noted to be clean, dry, and intact had a stronger association with completion of therapy than those that were not fully intact. Emphasis was placed on ensuring consistent practices with insertion, care, and maintenance, which contributed to more consistent outcomes between settings that insert, care for, and maintain devices. Nonmodifiable risk factors may remain.